Video_1_Copepod Grazing Influences Diatom Aggregation and Particle Dynamics.MP4 - Jordan Toullec; Dorothée Vincent; Laura Frohn; Philippe Miner; Manon Le Goff; Jérémy Devesa; Brivaëla Moriceau (2019)
In marine ecosystems, carbon export is driven by particle flux which is modulated by aggregation, remineralization, and grazing processes. Zooplankton contribute to the sinking flux through the egestion of fast sinking fecal pellets but may also attenuate the flux by tearing apart phytoplankton aggregates into small pieces through swimming activity or direct ingestion. Freely suspended cells, artificial monospecific aggregates from two different diatom species (Chaetoceros neogracile and Skeletonema marinoi) and natural aggregates of Melosira sp. were independently incubated with five different copepod species (Acartia clausi, Temora longicornis, Calanus helgolandicus, Euterpina acutifrons, and Calanus hyperboreus). During the grazing experiments initiated with free diatoms, E. acutifrons feeding activity evidenced by ingestion rates of 157 ± 155 ng Chl a ind –1 d –1 , induced a significant increase of S. marinoi aggregation. Transparent exopolymeric particles (TEP) production was only slightly boosted by the presence of grazers and turbulences created by swimming may be the main trigger of the aggregation processes. All copepods studied were able to graze on aggregates and quantitative estimates led to chlorophyll a ingestion rates (expressed in Chla a equivalent, i.e., the sum of chlorophyll a and pheopigments in their guts) ranging from 4 to 23 ng Chl a eq ind –1 d –1 . The relation between equivalent spherical diameters (ESDs) and sinking velocities of the aggregates did not significantly change after grazing, suggesting that copepod grazing did not affect aggregate density as also shown by Si:C and C:N ratios. Three main trends in particle dynamics could be identified and further linked to the copepod feeding behavior and the size ratio between prey and predators: (1) Fragmentation of S. marinoi aggregates by the cruise feeder T. longicornis and of Melosira sp. aggregates by C. hyperboreus at prey to predator size ratios larger than 15; (2) no change of particle dynamics in the presence of the detritic ...